The Effects of Recycled Tire Rubbers and Steel Fibers on the Performance of Self-compacting Alkali Activated Concrete - Eren, Necip Altay; Alzeebaree, Radhwan; Çevik, Abdulkadir; Niş, Anıl; Mohammedameen, Alaa; Gülşan, Mehmet Eren (Periodica Polytechnica Civil Engineering, 2021)
In this study, the effects of recycled tire rubbers (RTR) and steel fiber (SF) on the fresh and hardened state properties of the self-compacted alkali activated concrete (SCAAC) were investigated. The ground granulated blast furnace slag, 1 % hooked-end SF, and two types of RTR were utilized. The crumb rubbers (CR) and tire rubber chips (TCR) were used as a substation to natural aggregates at substation levels of 10 % and 15 %. The fresh state performances were evaluated by T50 value, slump flow, V-funnel, and L-Box tests, while mechanical performances were assessed through compressive, flexural, and splitting tensile strength tests. Also, detailed crack and microstructural analyses were conducted. The RTR adversely affected the fresh state properties, which reduced more with SF inclusions. Among the RTR, the TR specimens exhibited lower fresh state performance than the CR specimens. Similar mechanical strengths were obtained on the TR and CR specimens under the same replacement ratios. However, TR specimens exhibited higher deformation capacities than the CR specimens, when SF was utilized. The SCAAC specimens with 1 % SF and 15 % RTR showed more and wider flexural cracks, higher mechanical strength, and deformation capacity, which can be utilized in structural applications, particularly in high seismic zones.